Constructing knowledge societies : new challenges for tertiary education. - World Bank. (Washington, DC : World Bank, 2002)
This text's main focus is the exploration of the role of tertiary education in the development of a country's capacity to better integrate higher education with the world's increasingly knowledge-based economy. It also examines policy options that have the potential to enchance economic growth
Includes bibliographical references (p. 197-204).
oif 29/06/2016
Loans
Keywords: Education, Higher; Educational assistance